2003
DOI: 10.1016/s0736-0266(02)00144-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of femoral perfusion in a non‐traumatic rabbit osteonecrosis model with T2*‐weighted dynamic MRI

Abstract: We evaluated femoral perfusion in a non-traumatic rabbit serum sickness osteonecrosis (ON) model, using serial repetitive T2*-weighted (T2'W) dynamic magnetic resonance imaging (MRI) and investigated prediction of ON occurrence in early stages, comparing T2*W dynamic MRI with non-enhanced (T2-, T1-and fat suppression T1-weighted) and contrast-enhanced MRI. Early microcirculatory injury or necrotic lesion was detected in 0% of femora (extravasation, 0/6) at 72 h, 33%) (necrotic, 4/12) at 1 week and 100% (necrot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Neurogenic compression, non-traumatic reflex sympathetic dystrophy, and obstruction of venous return with localized hyperemia have been debated in the etiology of TBME [9], whereas a significant reduction or obliteration of blood supply is thought to be the major cause of non-traumatic femoral head AVN [10]. Since BME might be an associated finding in patients with AVN, some http://dx.doi.org/10.1016/j.ejrad.2014.07.017 0720-048X/© 2014 Elsevier Ireland Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…Neurogenic compression, non-traumatic reflex sympathetic dystrophy, and obstruction of venous return with localized hyperemia have been debated in the etiology of TBME [9], whereas a significant reduction or obliteration of blood supply is thought to be the major cause of non-traumatic femoral head AVN [10]. Since BME might be an associated finding in patients with AVN, some http://dx.doi.org/10.1016/j.ejrad.2014.07.017 0720-048X/© 2014 Elsevier Ireland Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…Verstraete et al [3] had elaborated on this aspect as well showing there was perfusion overlap between benign and malignant bone tumors. Moreover, 3 of the 4 cases were diagnosed as benign according to ADCs.…”
Section: Discussionmentioning
confidence: 98%
“…First pass images provide diagnostically useful information by depicting tissue vascularisation and perfusion [3] . Geirnaerdt et al [8] and Van et al [10] reported that there were more tumoral neovascularisation with higher permeability in malignant tumors than it existed in benign lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanically, ON may be induced by obstruction of the lateral epiphyseal blood vessels of femoral head (Oda et al 1996), or deep-freezing (Malizos et al 1993). Researchers have produced surgically induced experimental ON in rats (Oda et al 1996;Shabat et al 2004), rabbits (Kawamoto et al 2000;Kenzora et al 1978;Tsuji et al 2003), dogs (Malizos et al 1993), pigs (Schneider et al 2003), turkeys (Julian, 1985), and emu (Reed et al 2004). Although several experimental animal models have been developed for ON of the hip joint, there are limited animal models of SONK because it has been difficult to replicate the natural history of structural bone collapse seen in humans (Boss and Misselevich, 2003;Mihara and Hirano, 1998;Oda et al 1996;Reed et al 2004).…”
Section: Animal Models Of Sonkmentioning
confidence: 99%